PENGARUH KUALITAS SUMBER DAYA MANUSIA, PROFESIONALISME KERJA DAN WORK LIFE BALANCE TERHADAP KINERJA KARYAWAN PERUMDA AIR MINUM TIRTA HITA BULELENG - ANAK AGUNG NGURAH RESTU GAUTAMA; I GUSTI NGURAH KADEK ANGGA WIGUNA (Universitas Mahasaraswati K. Mataram, 2024)
Human resources are still a concern for organizational companies to survive. Having quality resources when we are able to be given responsibility and exercise authority, however,a number of problems were found related to the quality of HumanResources Quality,Professionalismof Work, Work Life Balance, Employee’s.Performance atPerumda Air MinumTirta Hita Buleleng, sothe examiner was interested inexamining the effect of Human ResourcesQuality, Professionalism ofWork and Work Life Balance,onemployee’s performance at PerumdaAir Minum Tirta Hita Buleleng. This test has an achievement to find outhow the influence of Human Resources Quality, Professionalism of Work, along with worklifebalance on the performanceof Perumda Air Minum TirtaHita Bulelengemployees. Thedata collection technique usedin this test is aquestionnaire to analyze the data quantitatively using,coefficient ofdetermination, multiple linear regressionanalysis, f-test analysis, t hypothesis test.The sample in this test is the central employees of Perumda Air Minum Tirta Hita Buleleng with a total of 136 respondents. Thedata analysis used inthis study is multiplelinear regressionanalysis, classical assumptiontest, f-test analysis and hypothesis t analysis. Based onthe results in this test, it can beconcluded thatthe quality of humanresources, workprofessionalism, andwork lifebalance have a significantpositive effect onemployee’sperformance.